The Promise of the New Learning Economy. Issue 4 (4th July 2019) - Gush, Jason; Smith, Jacksón
Abstract : Innovations that are transforming society at large can be important vehicles for change in the education sector as well. What advances does blockchain technology offer to the learners of today and tomorrow?